Improved packet loss concealment for PCM voice transmission over Internet Protocol network - Li, Qi (University of Ottawa (Canada), 2004)
In recent years, packet voice over the Internet Protocol (IP) network has become an attractive alternative to conventional public telephony. However, the Internet is a best-effort network, with no guarantee on its quality of service. A fundamental issue in real-time interactive voice transmissions over an unreliable Internet Protocol (IP) network is the loss, or late arrival of packets. Concealment algorithms, either transmitter or receiver based, are used to replace these lost packets. The packet loss concealment (PLC) techniques described in the standards ANSI TI.521 (Annex B) and ITU-T Rec. G.711 Appendix I produce a good performance for PCM coded speech. However, these algorithms do not use subsequent packets from the fitter buffer for reconstruction, which could further increase the PLC performance. The goal of this work is to develop an improved PLC algorithm for PCM coded speech, using the subsequent packet information when available. A method combining pitch prediction and Linear Prediction Coding (LPC) is used to estimate the missing voice packets.
Keywords: Engineering, Electronics and Electrical.